Currents and overvoltages caused by establishing and interrupting of ground faults in 10 kV network in the city of Nis - Vukelja, Petar; Mrvić, Jovan; Hrvić, Dejan (Proceedings, Electrical engineering institute "Nikola Tesla", 2012)
Abstract: This paper presents the results of experimental studies of ground fault currents and overvoltages that occur in the establishment and interruption of ground faults in an isolated part of the 10 kV distribution network, fed to the city of Nis, from four TS 35 kV/10 kV transformers. An analysis of the results was performed and those problems that occur in an isolated 10 kV network identified. The validity of the transition from a network with isolated to grounded star point 35 kV/10 kV  transformers was demonstrated
Keywords: distribution network 10 kV; overvoltage; ground fault current